A straw-type PE wood-plastic composite floor and its preparation process

By combining modified straw materials and flame retardant components, the problem of poor flame retardant performance of PE wood-plastic composite floors is solved, and higher flame retardant and mechanical properties are achieved, which broadens its application range.

CN118440509BActive Publication Date: 2025-02-18JIANGSU KENTIER WOOD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410585630.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2025-02-18
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

The flooring of existing PE wood-plastic composites has poor flame retardant performance and is difficult to meet the wider application needs.

Method used

Using modified straw materials and flame retardant components, the straw materials are modified by polyethylene-polysiloxane graft, and the flame retardant components are prepared using raw materials such as magnesium hydroxide, zinc borate and hexabromocyclododecane to prepare flame retardant components, uniformly After mixing, PE wood-plastic composite flooring is prepared by vulcanization process.

Benefits of technology

The flame retardancy and mechanical properties of PE wood-plastic composite flooring are improved, making it more widely used.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of floor preparation, and in particular to a straw-type PE wood-plastic composite material floor and a preparation process thereof. The straw-type PE wood-plastic composite material comprises the following raw materials by weight: 35-45 parts of modified straw material, 25-35 parts of polyethylene material, and 25-35 parts of flame retardant components. The invention classifies wheat straw first and then modifies the straw, thereby improving the problem of strong water absorption of the final PE wood-plastic composite material, and at the same time, modified straw materials of different sizes can be mixed more fully and thoroughly in the system, and there is a strong interaction between maleic anhydride grafted high-density polyethylene and the modified straw material. In addition, the flame retardant component is compounded and used, and magnesium hydroxide modified by high-density polyethylene and KH570 will not agglomerate in the system, and the flame retardancy can be improved while the mechanical properties can be improved. Therefore, the straw-type PE wood-plastic composite material floor prepared by the invention has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of floor preparation, in particular to a straw-type PE wood-plastic composite material floor and a preparation process thereof. Background Art

[0002] Wood-Plastic Composites (WPC) is a new type of material prepared by mixing wood powder and plastic powder as raw materials. WPC has the dual advantages of wood and plastic, but the flammability of WPC limits its wider application. PE wood-plastic, that is, PE wood-plastic composites, is a new wood material made by using polyethylene (PE) instead of the usual resin adhesive, and waste plant fibers such as wood powder, rice husks, straw and other additives through a secondary granulation method. PE wood-plastic has the following advantages: green and recyclable, excellent mechanical properties, water resistance, excellent corrosion resistance and weather resistance, long service life, low subsequent maintenance costs, etc., but PE wood-plastic also has many disadvantages, such as high density (1.35-1.40)), low flame retardancy, etc.

[0003] A Chinese invention patent with publication number CN103525110B discloses a high-strength PE wood-plastic composite material and a preparation method thereof. The invention prepares the PE wood-plastic composite material by mixing waste PE plastic, plant fiber powder, thermoplastic elastomer, interfacial compatibilizer and reinforcing filler. However, since no flame retardant component is added in the method, the flame retardant performance of the finally prepared PE wood-plastic composite material is poor. Therefore, a Chinese invention patent with publication number CN104817783B discloses a multifunctional lightweight wood-plastic composite material for modern home and a preparation method thereof. The method prepares the multifunctional lightweight wood-plastic composite material by mixing PVC SG-8, light calcium carbonate, hydrated magnesium oxide, straw powder, calcium-zinc composite stabilizer and the like. Although the method improves the flame retardant performance of the wood-plastic composite material, since too much filler is added during the preparation process, the filler is very easy to agglomerate and unevenly distributed in the system, which makes the performance of the final product poor.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a straw-type PE wood-plastic composite material floor and a preparation process thereof. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a straw-type PE wood-plastic composite material floor and a preparation process thereof, so as to solve the problem of poor flame retardancy of PE wood-plastic composite materials in the prior art.

[0006] Based on the above purpose, the present invention provides a straw-type PE wood-plastic composite material floor and a preparation process thereof.

[0007] A straw-type PE wood-plastic composite floor, characterized in that it comprises the following raw materials by weight: 35-45 parts of modified straw material, 25-35 parts of polyethylene material, and 25-35 parts of flame retardant component;

[0008] The modified straw material is a mixture of polyethylene-polysiloxane grafted wheat straw;

[0009] The wheat straw mixture is obtained by mixing wheat straw of 40-60 mesh, wheat straw of 60-80 mesh and wheat straw of >80 mesh in a mass ratio of 40-50:10-20:1-6;

[0010] The flame retardant component is prepared by taking magnesium hydroxide, zinc borate and hexabromocyclododecane as raw materials.

[0011] Preferably, the preparation method of the modified straw material is as follows:

[0012] Step S1. Mix wheat straw with mesh sizes of 40-60 mesh, wheat straw with mesh sizes of 60-80 mesh, and wheat straw with mesh sizes greater than 80 mesh to obtain a wheat straw mixture;

[0013] Step S2. Place the wheat straw mixture into the pretreatment agent, stir evenly, treat at 100-110°C for 3-4h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 50-60°C for 1-2h to obtain the pretreated straw material;

[0014] Step S3. Add the pretreated straw material, silica particles, vinyl triethoxysilane and 0.1 mol / L sodium hydroxide solution to ethanol, stir evenly, ultrasonically disperse for 25-35 min, treat in a muffle furnace at 100-110° C. for 1-1.5 h, and after the reaction is completed, filter and dry in a vacuum drying oven at 70-80° C. for 30-40 min to obtain a polysiloxane-modified straw material;

[0015] Step S4. The polysiloxane-grafted straw material, polyethylene, chlorobenzene and Karstedt catalyst solution are uniformly mixed, stirred at 110-120° C. for 10-12 h under nitrogen protection, washed with chlorobenzene for 3-5 times, and dried to obtain the modified straw material.

[0016] Preferably, the pretreatment agent in step S2 is a mixture of sodium sulfide, sodium hydroxide and distilled water in a mass ratio of 2-3:1.5-1.8:200.

[0017] Preferably, the mass ratio of the wheat straw mixture to the pretreatment agent in step S2 is 20-30:150-160.

[0018] Preferably, in step S3, the dosage ratio of the treated straw material, silica particles, vinyltriethoxysilane, 0.1 mol / L sodium hydroxide solution and ethanol is 25-35 g: 0.5-1.5 g: 15-25 mL: 25-35 mL: 350-450 mL.

[0019] Preferably, in step S4, the usage ratio of the polysiloxane-grafted straw material, polyethylene, chlorobenzene and Karstedt catalyst solution is 10-20 g: 2-3 g: 100-120 mL: 0.03-0.04 g.

[0020] Preferably, the preparation method of the flame retardant component is as follows:

[0021] KH570 is added dropwise to magnesium hydroxide, and stirred at a speed of 1100-1200 r / min for 50-60 min. High-density polyethylene and hexabromocyclododecane are added, and the mixture is mixed and then extruded and granulated to obtain a flame retardant component.

[0022] Preferably, the mass ratio of KH570, magnesium hydroxide, high-density polyethylene and hexabromocyclododecane is 0.3-0.5g: 8-12g: 2-4g: 24-34g.

[0023] Preferably, the polyethylene material is high-density polyethylene grafted with maleic anhydride.

[0024] A preparation process of a straw-type PE wood-plastic composite material floor is as follows:

[0025] Step S11. The modified straw material, the polyethylene material and the flame retardant component are uniformly mixed, added into a torque rheometer at a speed of 50-60 r / min, and mixed at 140-150° C. for 10-15 min to obtain a pre-mixed material block;

[0026] Step S12. Place the initially mixed material block in a vulcanizer, press the plate at 150-160° C., deflate when the working pressure reaches 10 MPa, repeat 4-5 times, maintain the working pressure at 10-15 MPa, and the deflation pressure at 8.5 MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 5-10 MPa for 10-20 minutes to obtain a straw-type PE wood-plastic composite material floor.

[0027] Beneficial effects of the present invention:

[0028] The modified straw material provided by the present invention is obtained by grafting and modifying straw materials of different sizes with polysiloxane and polyethylene. The straw materials crushed into different sizes can be mixed evenly and thoroughly in the system. After modification, the groups on the surface are reacted, and since there is a strong interaction between the polymer chains on the surface and the polyethylene material, the modified straw material is evenly distributed in the system, thereby improving the mechanical properties of the PE wood-plastic composite material floor.

[0029] The flame retardant component provided by the present invention has good compatibility with the system and high flame retardancy, and can also be used as a reinforcing filler to further improve the mechanical properties of the PE wood-plastic composite material floor. Therefore, the PE wood-plastic composite material floor prepared by the present invention has broad application prospects. DETAILED DESCRIPTION

[0030] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0031] Embodiment 1: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0032] Step S1. 40 g of wheat straw with a mesh size of 40-60 mesh, 10 g of wheat straw with a mesh size of 60-80 mesh, and 1 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0033] Step S2. 2 g of sodium sulfide, 1.5 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0034] Step S3. Put 20g of the wheat straw mixture into 150g of the pretreatment agent, stir evenly, treat at 100°C for 3h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 50°C for 1h to obtain the pretreated straw material;

[0035] Step S4. 25 g of pretreated straw material, 0.5 g of silica particles, 15 mL of vinyl triethoxysilane and 25 mL of 0.1 mol / L sodium hydroxide solution were added to 350 mL of ethanol, stirred evenly, ultrasonically dispersed for 25 min, treated in a muffle furnace at 100 ° C for 1 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 70 ° C for 30 min to obtain a polysiloxane-modified straw material;

[0036] Step S5. 10 g of polysiloxane-grafted straw material, 2 g of polyethylene, 100 mL of chlorobenzene and 0.032 g of Karstedt catalyst solution were mixed evenly, stirred at 110° C. for 10 h under nitrogen protection, washed with chlorobenzene three times, and dried to obtain a modified straw material;

[0037] Step S6. 0.3 g KH570 was added dropwise to 8 g magnesium hydroxide, stirred at a speed of 1100 r / min for 50 min, 2 g high-density polyethylene and 24 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0038] Step S7. 35 g of modified straw material, 25 g of maleic anhydride grafted high-density polyethylene material and 25 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 50 r / min and mixed at 140°C for 10 min to obtain a pre-mixed material block;

[0039] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 150°C, deflate when the working pressure reaches 10MPa, repeat 4 times, maintain the working pressure at 10MPa, deflate at 8.5MPa, place in a cold pressing flat plate vulcanizer at 5MPa for 10min, and obtain a straw-type PE wood-plastic composite floor.

[0040] Embodiment 2: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0041] Step S1. 42 g of wheat straw with a mesh size of 40-60 mesh, 12 g of wheat straw with a mesh size of 60-80 mesh, and 2 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0042] Step S2. 2.2 g of sodium sulfide, 1.5 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0043] Step S3. Add 22 g of the wheat straw mixture into 152 g of the pretreatment agent, stir evenly, treat at 102° C. for 3.2 h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 52° C. for 1.2 h to obtain the pretreated straw material;

[0044] Step S4. 27 g of pretreated straw material, 0.7 g of silica particles, 17 mL of vinyl triethoxysilane and 27 mL of 0.1 mol / L sodium hydroxide solution were added to 370 mL of ethanol, stirred evenly, ultrasonically dispersed for 27 min, treated in a muffle furnace at 102 ° C for 1.1 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 72 ° C for 32 min to obtain a polysiloxane-modified straw material;

[0045] Step S5. 12 g of polysiloxane-grafted straw material, 2.2 g of polyethylene, 104 mL of chlorobenzene and 0.034 g of Karstedt catalyst solution were mixed evenly, stirred at 112° C. for 10.5 h under nitrogen protection, washed with chlorobenzene three times, and dried to obtain a modified straw material;

[0046] Step S6. 0.34 g KH570 was added dropwise to 9 g magnesium hydroxide, stirred at a speed of 1120 r / min for 52 min, 2.4 g high-density polyethylene and 26 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0047] Step S7. 37 g of modified straw material, 27 g of maleic anhydride grafted high-density polyethylene material and 27 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 52 r / min and mixed at 142° C. for 11 min to obtain a pre-mixed material block;

[0048] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 152°C, deflate when the working pressure reaches 10MPa, repeat 4 times, maintain the working pressure at 11MPa, and the deflation pressure at 8.5MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 6MPa for 12 minutes to obtain a straw-type PE wood-plastic composite floor.

[0049] Embodiment 3: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0050] Step S1. 44 g of wheat straw with a mesh size of 40-60 mesh, 14 g of wheat straw with a mesh size of 60-80 mesh, and 3 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0051] Step S2. 2.4 g of sodium sulfide, 1.6 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0052] Step S3. 24 g of the wheat straw mixture was placed in 154 g of the pretreatment agent, stirred evenly, treated at 104°C for 3.4 h, cooled after the reaction was completed, adjusted to neutral, filtered and separated, and then dried in an oven at 54°C for 1.4 h to obtain the pretreated straw material;

[0053] Step S4. 29 g of pretreated straw material, 0.9 g of silica particles, 19 mL of vinyl triethoxysilane and 29 mL of 0.1 mol / L sodium hydroxide solution were added to 390 mL of ethanol, stirred evenly, ultrasonically dispersed for 29 min, treated in a muffle furnace at 104 ° C for 1.2 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 74 ° C for 34 min to obtain a polysiloxane-modified straw material;

[0054] Step S5. 14 g of polysiloxane-grafted straw material, 2.4 g of polyethylene, 108 mL of chlorobenzene and 0.036 g of Karstedt catalyst solution were mixed evenly, stirred at 114 ° C for 11 h under nitrogen protection, washed with chlorobenzene 4 times, and dried to obtain a modified straw material;

[0055] Step S6. 0.38 g KH570 was added dropwise to 10 g magnesium hydroxide, stirred at a speed of 1140 r / min for 54 min, 2.8 g high-density polyethylene and 28 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0056] Step S7. 39 g of modified straw material, 29 g of maleic anhydride grafted high-density polyethylene material and 29 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 54 r / min and mixed at 144° C. for 12 min to obtain a pre-mixed material block;

[0057] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 154°C, deflate when the working pressure reaches 10MPa, repeat 4 times, maintain the working pressure at 12MPa, and the deflation pressure at 8.5MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 7MPa for 14 minutes to obtain a straw-type PE wood-plastic composite floor.

[0058] Example 4: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0059] Step S1. 46 g of wheat straw with a mesh size of 40-60 mesh, 16 g of wheat straw with a mesh size of 60-80 mesh, and 4 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0060] Step S2. 2.6 g of sodium sulfide, 1.7 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0061] Step S3. Add 26 g of the wheat straw mixture into 156 g of the pretreatment agent, stir evenly, treat at 106° C. for 3.6 h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 56° C. for 1.6 h to obtain the pretreated straw material;

[0062] Step S4. 31 g of pretreated straw material, 1.1 g of silica particles, 21 mL of vinyl triethoxysilane and 31 mL of 0.1 mol / L sodium hydroxide solution were added to 410 mL of ethanol, stirred evenly, ultrasonically dispersed for 31 min, treated in a muffle furnace at 106 ° C for 1.3 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 76 ° C for 36 min to obtain a polysiloxane-modified straw material;

[0063] Step S5. 16 g of polysiloxane-grafted straw material, 2.6 g of polyethylene, 112 mL of chlorobenzene and 0.036 g of Karstedt catalyst solution were mixed evenly, stirred at 116° C. for 11.5 h under nitrogen protection, washed with chlorobenzene 4 times, and dried to obtain a modified straw material;

[0064] Step S6. 0.42 g KH570 was added dropwise to 11 g magnesium hydroxide, stirred at a speed of 1160 r / min for 56 min, 3.2 g high-density polyethylene and 30 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0065] Step S7. 41 g of modified straw material, 31 g of maleic anhydride grafted high-density polyethylene material and 31 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 56 r / min and mixed at 146° C. for 13 min to obtain a pre-mixed material block;

[0066] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 156°C, deflate when the working pressure reaches 10MPa, repeat 5 times, maintain the working pressure at 13MPa, and the deflation pressure at 8.5MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 8MPa for 16 minutes to obtain a straw-type PE wood-plastic composite floor.

[0067] Embodiment 5: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0068] Step S1. 48 g of wheat straw with a mesh size of 40-60 mesh, 18 g of wheat straw with a mesh size of 60-80 mesh, and 5 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0069] Step S2. 2.8 g of sodium sulfide, 1.8 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0070] Step S3. Add 28g of the wheat straw mixture into 158g of the pretreatment agent, stir evenly, treat at 108°C for 3.8h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 58°C for 1.8h to obtain the pretreated straw material;

[0071] Step S4. 33 g of pretreated straw material, 1.3 g of silica particles, 23 mL of vinyl triethoxysilane and 33 mL of 0.1 mol / L sodium hydroxide solution were added to 430 mL of ethanol, stirred evenly, ultrasonically dispersed for 33 min, treated in a muffle furnace at 108 ° C for 1.4 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 78 ° C for 38 min to obtain a polysiloxane-modified straw material;

[0072] Step S5. 18 g of polysiloxane-grafted straw material, 2.8 g of polyethylene, 116 mL of chlorobenzene and 0.038 g of Karstedt catalyst solution were mixed evenly, stirred at 118 ° C for 12 h under nitrogen protection, washed with chlorobenzene 5 times, and dried to obtain a modified straw material;

[0073] Step S6. 0.46 g KH570 was added dropwise to 11 g magnesium hydroxide, stirred at a speed of 1180 r / min for 58 min, 3.6 g high-density polyethylene and 30 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0074] Step S7. 43 g of modified straw material, 33 g of maleic anhydride grafted high-density polyethylene material and 33 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 58 r / min and mixed at 148° C. for 14 min to obtain a pre-mixed material block;

[0075] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 158°C, deflate when the working pressure reaches 10MPa, repeat 5 times, maintain the working pressure at 14MPa, and the deflation pressure at 8.5MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 9MPa for 18 minutes to obtain a straw-type PE wood-plastic composite floor.

[0076] Example 6: A preparation process of a straw-type PE wood-plastic composite material floor, comprising the following steps:

[0077] Step S1. 50 g of wheat straw with a mesh size of 40-60 mesh, 20 g of wheat straw with a mesh size of 60-80 mesh, and 6 g of wheat straw with a mesh size of >80 mesh are mixed to obtain a wheat straw mixture;

[0078] Step S2. 3 g of sodium sulfide, 1.8 g of sodium hydroxide and 200 g of distilled water were mixed to obtain a pretreatment agent;

[0079] Step S3. 30 g of the wheat straw mixture was placed in 160 g of the pretreatment agent, stirred evenly, treated at 110° C. for 4 h, cooled after the reaction was completed, adjusted to neutral, filtered and separated, and then dried in an oven at 60° C. for 2 h to obtain the pretreated straw material;

[0080] Step S4. 35 g of pretreated straw material, 1.5 g of silica particles, 25 mL of vinyl triethoxysilane and 35 mL of 0.1 mol / L sodium hydroxide solution were added to 450 mL of ethanol, stirred evenly, ultrasonically dispersed for 35 min, treated in a muffle furnace at 110 ° C for 1.5 h, and after the reaction was completed, filtered and placed in a vacuum drying oven at 80 ° C for 40 min to obtain a polysiloxane-modified straw material;

[0081] Step S5. 20 g of polysiloxane-grafted straw material, 3 g of polyethylene, 120 mL of chlorobenzene and 0.04 g of Karstedt catalyst solution were mixed evenly, stirred at 120 ° C for 12 h under nitrogen protection, washed with chlorobenzene 5 times, and dried to obtain a modified straw material;

[0082] Step S6. 0.5 g KH570 was added dropwise to 12 g magnesium hydroxide, stirred at a speed of 1200 r / min for 60 min, 4 g high-density polyethylene and 34 g hexabromocyclododecane were added, mixed and extruded into granules to obtain a flame retardant component;

[0083] Step S7. 45 g of modified straw material, 35 g of maleic anhydride grafted high-density polyethylene material and 35 g of flame retardant component were uniformly mixed, added to a torque rheometer at a speed of 60 r / min and mixed at 150° C. for 15 min to obtain a pre-mixed material block;

[0084] Step S8. Place the initially mixed material block in a vulcanizer, press the plate at 160°C, deflate when the working pressure reaches 10MPa, repeat 5 times, maintain the working pressure at 15MPa, and the deflation pressure at 8.5MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 10MPa for 20 minutes to obtain a straw-type PE wood-plastic composite material floor.

[0085] Comparative Example 1:

[0086] Compared with Example 1, this comparative example only replaces the "wheat straw mixture" with "wheat straw with mesh size > 80 mesh", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a straw-type PE wood-plastic composite material floor is obtained.

[0087] Comparative Example 2:

[0088] Compared with Example 1, this comparative example only replaces the "modified straw material" with "polysiloxane-modified straw material", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a straw-type PE wood-plastic composite material floor is obtained.

[0089] Comparative Example 3:

[0090] Compared with Example 1, this comparative example only replaces the "modified straw material" with "wheat straw", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a straw-type PE wood-plastic composite material floor is obtained.

[0091] Comparative Example 4:

[0092] Compared with Example 1, this comparative example only replaces the "maleic anhydride grafted high-density polyethylene material" with "high-density polyethylene material with the same molecular weight", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a straw-type PE wood-plastic composite material floor is obtained.

[0093] Comparative Example 5:

[0094] Compared with Example 1, this comparative example only replaces the "flame retardant component" with "magnesium hydroxide", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a straw-type PE wood-plastic composite material floor is obtained.

[0095] Performance Testing:

[0096] UL-94 vertical combustion test: CZF-3 horizontal vertical combustion instrument (Nanjing Jiangning Analytical Instrument Factory) was used to test in accordance with GB / T2048-1996 standard. The size of the sample was 120mm×13mm×3mm.

[0097] Limiting oxygen index (LOI) test: HC-2A oxygen index tester (Nanjing Jiangning Analytical Instrument Factory) was used to test according to ASTMD2863 standard. The size of the sample was 120mm×6.5mm×3mm.

[0098] Bending strength test: ZBC1400-A pendulum bending tester (Mets Industrial Systems Co., Ltd.) was used according to the national standard GB / T9341-2008. The pendulum energy used was 2.75J and the test temperature was 25±2℃.

[0099] Tensile strength test: CMT4303 electronic universal testing machine (Shenzhen Xinsansi Material Testing Co., Ltd.) was used, according to the national standard GB / T1040-96, the tensile rate used in the experiment was 10mm / min, and the test temperature was 25±2℃;

[0100] The results are shown in Table 1 below:

[0101] Table 1

[0102] project UL-94 LOI Bending strength / MPa Tensile strength / MPa Example 1 V-0 34.8 22.7 33.8 Example 2 V-0 32.4 21.1 32.3 Example 3 V-0 33.6 20.5 31.8 Example 4 V-0 34.1 22.6 33.9 Example 5 V-0 32.5 22.2 33.4 Example 6 V-0 33.3 21.9 32.5 Comparative Example 1 V-0 31.9 19.4 30.3 Comparative Example 2 V-1 30.5 18.5 29.7 Comparative Example 3 V-1 29.2 15.5 26.8 Comparative Example 4 V-0 31.2 14.4 25.5 Comparative Example 5 V-2 28.5 13.5 24.4

[0103] Data Analysis:

[0104] It can be seen from Table 1 that the straw-type PE wood-plastic composite material floor prepared by the present invention has high flame retardancy, high bending strength and tensile strength. This is because the present invention first crushes the wheat straw into different sizes, and then undergoes polysiloxane and polyethylene grafting modification. The straw materials crushed into different sizes can be mixed evenly and thoroughly inside the system. After modification, the groups on its surface are reacted, and there is a strong interaction between the polymer chains on its surface and the polyethylene material, so that the modified straw material is evenly distributed in the system, thereby improving the mechanical properties of the PE wood-plastic composite material floor.

[0105] In addition, the flame retardant component provided by the present invention is high-density polyethylene modified magnesium hydroxide, which has good compatibility with the system and is therefore not easy to agglomerate, which makes the finally prepared straw-type PE wood-plastic composite material have higher flame retardancy. At the same time, the flame retardant component can also be used as a reinforcing filler to further improve the mechanical properties of the PE wood-plastic composite floor. Therefore, the PE wood-plastic composite floor prepared by the present invention has broad application prospects.

[0106] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0107] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A straw-type PE wood-plastic composite floor, characterized in that: The invention comprises the following raw materials by weight: 35-45 parts of modified straw material, 25-35 parts of polyethylene material, and 25-35 parts of flame retardant component; The modified straw material is a mixture of polyethylene-polysiloxane grafted wheat straw; The wheat straw mixture is obtained by mixing wheat straw of 40-60 mesh, wheat straw of 60-80 mesh and wheat straw of >80 mesh in a mass ratio of 40-50:10-20:1-6; The flame retardant component is prepared from magnesium hydroxide and hexabromocyclododecane as raw materials; The preparation method of the modified straw material is as follows: Step S1. Mix wheat straw with mesh sizes of 40-60 mesh, wheat straw with mesh sizes of 60-80 mesh, and wheat straw with mesh sizes greater than 80 mesh to obtain a wheat straw mixture; Step S2. Place the wheat straw mixture into the pretreatment agent, stir evenly, treat at 100-110°C for 3-4h, cool after the reaction, adjust to neutral, filter and separate, and then dry in an oven at 50-60°C for 1-2h to obtain the pretreated straw material; Step S3. Add the pretreated straw material, silica particles, vinyl triethoxysilane and 0.1 mol / L sodium hydroxide solution to ethanol, stir evenly, ultrasonically disperse for 25-35 min, treat in a muffle furnace at 100-110° C. for 1-1.5 h, and after the reaction is completed, filter and dry in a vacuum drying oven at 70-80° C. for 30-40 min to obtain a polysiloxane-modified straw material; Step S4. The polysiloxane-grafted straw material, polyethylene, chlorobenzene and Karstedt catalyst solution are mixed evenly, stirred at 110-120° C. for 10-12 h under nitrogen protection, washed with chlorobenzene 3-5 times, and dried to obtain a modified straw material; The preparation method of the flame retardant component is as follows: KH570 is added dropwise to magnesium hydroxide, stirred at a speed of 1100-1200 r / min for 50-60 min, high-density polyethylene and hexabromocyclododecane are added, mixed and then extruded and granulated to obtain a flame retardant component; The polyethylene material is high-density polyethylene grafted with maleic anhydride.

2. The straw-type PE wood-plastic composite floor according to claim 1, characterized in that: The pretreatment agent in step S2 is obtained by mixing sodium sulfide, sodium hydroxide and distilled water in a mass ratio of 2-3:1.5-1.8:

200.

3. The straw-type PE wood-plastic composite floor according to claim 1, characterized in that: The mass ratio of the wheat straw mixture to the pretreatment agent in step S2 is 20-30:150-160.

4. The straw-type PE wood-plastic composite floor according to claim 1, characterized in that: In step S3, the pretreated straw material, silicon dioxide particles, vinyl triethoxysilane, 0.1 mol / L sodium hydroxide solution and ethanol are used in a ratio of 25-35 g: 0.5-1.5 g: 15-25 mL: 25-35 mL: 350-450 mL.

5. The straw-type PE wood-plastic composite floor according to claim 1, characterized in that: In step S4, the usage ratio of the polysiloxane-grafted straw material, polyethylene, chlorobenzene and Karstedt catalyst solution is 10-20 g: 2-3 g: 100-120 mL: 0.03-0.04 g.

6. The straw-type PE wood-plastic composite material floor according to claim 1, characterized in that: The mass ratio of KH570, magnesium hydroxide, high-density polyethylene and hexabromocyclododecane is 0.3-0.5g: 8-12g: 2-4g: 24-34g.

7. A straw-type PE wood-plastic composite floor according to any one of claims 1 to 6, characterized in that: The preparation process of the straw-type wood-plastic composite material floor is as follows: Step S11. The modified straw material, the polyethylene material and the flame retardant component are uniformly mixed, added into a torque rheometer at a speed of 50-60 r / min, and mixed at 140-150° C. for 10-15 min to obtain a pre-mixed material block; Step S12. Place the initially mixed material block in a vulcanizer, press the plate at 150-160° C., deflate when the working pressure reaches 10 MPa, repeat 4-5 times, maintain the working pressure at 10-15 MPa, and the deflation pressure at 8.5 MPa. After 5 minutes, place it in a cold pressing flat plate vulcanizer and maintain the pressure at 5-10 MPa for 10-20 minutes to obtain a straw-type PE wood-plastic composite material floor.

Citation Information

Patent Citations

  • A kind of high-strength PE wood-plastic composite material and preparation method thereof

    CN103525110B

  • A multifunctional lightweight wood-plastic composite material for modern homes and its preparation method

    CN104817783B

  • Flame retardant micro-foamed all plastic wood-like material and its preparation method

    CN102408642A

  • Flame retardant high-wood content wood-plastic composite material and preparation method thereof

    CN102408736A